An Empirical Study on Developing the Tourism Potentials of Fairs and Festivals in Odisha in India - MOHANTY, Rojalin; SAMAL, Ansuman (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
Numerous studies on the appeal of tourist sites have been done. However, little study has been conducted on festival attractiveness and its effect on place attachment. This study adopted a mixed-methods strategy to examine the festivals in Odisha. Travel and tourism have become essential economic activities throughout the world in this globalization market. Festivals have recently grown in number, variety, and popularity, making them one of the strongest parts of the tourism industry. During tourism activities, tourists pay close attention to how attractive something is. The festival’s appeal is one of the most important things that determines whether or not a tourist will go and take part in activities. Also, the appeal of a festival can makes tourists more likely to come back, which is the key to the success of festival activities. This paper sought to determine the role of tourism as a long-run economic growth mechanism in Odisha. The Government of Odisha promotes tourism, but the focus remains on the golden triangle, which includes Puri, Konark, and Bhubaneswar. Without a doubt, these locations are well-equipped to meet the needs of both domestic and foreign tourists. Other beautiful places in Odisha still are largely unknown to tourists. In this paper, we try to demonstrate the overall importance of various fairs and festivals for the development of tourism and relate the significance of fairs and festivals.